La isla de James y el biocentrismo como utopía en El dios de Darwin de Sabina Berman - Parrilla Sotomayor, Eduardo E. (Romanica Silesiana)
<!–EndFragment–>In this article I delve into a recently published novel, El dios de Darwin (2014), written by Sabina Berman. Its purpose revolves around the utopic implications of the author´s esthetic project. First, I examine the relationship between the two plots which are intertwined in the novel. One of them takes place nowadays, around 2012; the other happens in 1876, in the decline of Darwin’s life, since he is the main character. El dios de Darwin is the story of a secret document found in Westminster Abbey by Antonio Márquez, a zoologist. A moment before his murder by a fundamentalist cell in Dubai, he attains to send by email fragments of the secret document to three other pro‑evolutionist friends. One of them is Karen Nieto, the main character of the contemporary plot. Struggling against Franco, Márquez’s former lover, who was a spy of a fundamentalist organization, Nieto at the end manages to rescue the secret document, he attempted to destroy. Within the second plot, the secret document (Theological Autobiography) and the circumstances of it being written by Darwin are interspersed until the end. The Autobiography was verily brought to light from censorship by Nora Barlow (1995), Darwin’s great‑granddaughter. The story unravels the unknown conversion to agnosticism experienced by the British naturalist. Since the novel is rich enough in scientific data and demonstrations extracted from The Origins of Species, The Descend of Man and the authentic Autobiography, I establish a parallelism between Darwin’s revolutionary contribution and the set of ideas about planetary ethics posed by the Brazilian theologian, Leonardo Boff. Key words: Darwin, natural morality, planetary ethics, Sabina Berman